Antiadipogenic effects of a standardized quassinoids-enriched fraction and eurycomanone from Eurycoma longifolia - Balan, D.; Chan, Kit Lam; Murugan, Dharmani Devi; AbuBakar, Sazaly; Wong, Pooi Fong (Wiley, 2018)
Bioactive compounds of Eurycoma longifolia (EL) jack were previously shown to reduce omentum fat mass and oestradiol-induced fatty uterine adhesion in rats. However, the exact role of EL on adipogenesis remains unknown. This study sought to investigate the effects of an EL standardized quassinoids-enriched fraction (SQEL) and the pure compound, eurycomanone, on adipogenesis in 3T3-L1 preadipocyte cells. 3T3-L1 cells were induced to differentiate and treated for 8 days. The treatment reduced intracellular accumulation of lipid droplets and triglycerides in the differentiating adipocytes and induced lipolysis in matured adipocytes. The expressions of adipogenic transcription factors and markers were also significantly downregulated during the early stage of differentiation. Furthermore, SQEL also suppressed body weight gain, decreased epididymal and perirenal fat pad mass and size, and reduced the accumulation of fat in the livers of C57BL/6J mice fed with normal or high-fat diet that were concurrently given 5 mg/kg and 10 mg/kg (i.p) of SQEL for 12 weeks. SQEL also improved glucose intolerance and decreased the elevated total cholesterol and triglyceride levels in these mice groups. These findings suggest that SQEL could be explored as an alternative pharmacologic agent inhibiting adipogenesis for the prevention of obesity.